2013
DOI: 10.1261/rna.038638.113
|View full text |Cite
|
Sign up to set email alerts
|

The spliceosome catalyzes debranching in competition with reverse of the first chemical reaction

Abstract: Splicing of nuclear pre-mRNA occurs via two steps of the transesterification reaction, forming a lariat intermediate and product. The reactions are catalyzed by the spliceosome, a large ribonucleoprotein complex composed of five small nuclear RNAs and numerous protein factors. The spliceosome shares a similar catalytic core structure with that of fungal group II introns, which can self-splice using the same chemical mechanism. Like group II introns, both catalytic steps of pre-mRNA splicing can efficiently rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Instead, in the spliceosome, we noticed that a putative K1 cavity essentially identical to the one of group II intron exists between U6-snRNA residues G52, A59, G60, and U80 ( Figure 5 ; Table S2 ). Although not modeled in the current structures, a potassium ion could optimally fit this putative K1 site at least at certain steps of the catalytic cycle, which would explain the spliceosomal dependence on potassium for splicing and debranching ( Hardy et al., 1984 , Tseng and Cheng, 2013 ). In addition, Lys611 (PROCN domain of the Prp8 subunit [ Staub et al., 2004 ], Data S1 ), which stabilizes the curvature of the intron backbone (U2 and U4) proximal to the splicing junction in the C complex, and/or conserved Arg614 (Prp8), which makes contacts with the exon in the C ∗ complex ( Figures 2 and 5 ; Table S2 ), seem to constitute optimal spliceosomal counterparts of K2.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, in the spliceosome, we noticed that a putative K1 cavity essentially identical to the one of group II intron exists between U6-snRNA residues G52, A59, G60, and U80 ( Figure 5 ; Table S2 ). Although not modeled in the current structures, a potassium ion could optimally fit this putative K1 site at least at certain steps of the catalytic cycle, which would explain the spliceosomal dependence on potassium for splicing and debranching ( Hardy et al., 1984 , Tseng and Cheng, 2013 ). In addition, Lys611 (PROCN domain of the Prp8 subunit [ Staub et al., 2004 ], Data S1 ), which stabilizes the curvature of the intron backbone (U2 and U4) proximal to the splicing junction in the C complex, and/or conserved Arg614 (Prp8), which makes contacts with the exon in the C ∗ complex ( Figures 2 and 5 ; Table S2 ), seem to constitute optimal spliceosomal counterparts of K2.…”
Section: Discussionmentioning
confidence: 99%
“…Because IEs are always found on the coding strand, new copies have been hypothesized to arise by intron RNA transposition through reverse splicing ( Tseng and Cheng 2008 , 2013 ) into an mRNA followed by reverse transcription of the RNA to cDNA ( Verhelst et al 2013 ) and homologous recombination. At the same time, a well-accepted model for intron removal invokes reverse transcription of spliced mRNA followed by homologous recombination ( Fink 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…After assembly initiation, the spliceosome can switch between different catalytic conformations that favor forward or reverse progress [ 41 ]. The splicing catalytic process is iso-energetic and driven by numerous ATPases, resulting in two transesterification processes that are both reversible in the proper ionic environment [ 63 , 64 ]. Recent single-molecule research on spliceosome assembly has revealed that almost all of the steps in splicing are reversible [ 65 , 66 ].…”
Section: Noise In Splicing: Where Does It Come From?mentioning
confidence: 99%